Analysis Of Factors Affecting Loyalty In KUR Askrindo Syariah Guarantee Products At Bank Syariah Indonesia, Makassar Region - Avianto Arbi Santoso; Yana Fajriah; Rezki Arianty Akoh (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This research aims to analyze the factors influencing loyalty toward KUR (People’s Business Credit) guarantee products offered by Askrindo Syariah at Bank Syariah Indonesia (BSI) in the Makassar Region. The study explores four independent variables: service quality, technological innovation, institutional reputation, and collaboration effectiveness. The research adopts a quantitative approach with a cross-sectional design. Data were collected through questionnaires distributed to 30 branch managers of BSI who utilize Askrindo Syariah’s KUR guarantee products during 2023–2024. Statistical analysis was conducted using multiple linear regression via SPSS. The results indicate that service quality, technological innovation, institutional reputation, and collaboration effectiveness have positive and significant effects on loyalty, both partially and simultaneously. The adjusted R² value of 0.744 shows that 74.4% of the variance in loyalty can be explained by the four variables. These findings highlight the importance of enhancing digital innovation, institutional trust, and inter-institutional collaboration to sustain long-term partnerships in Islamic financial ecosystems